Effect of Irisin on LIF and integrin αvβ3 in rats of implantation failure - Li Zhou; Chenggang Li; Xiangshu Liu; Tao Zhang (BMC, 2021)
Abstract Objective The aim of this study is to investigate the effect of irisin on leukemia inhibitory factor (LIF) and integrin αvβ3 in implantation failure uterus. Methods Early pregnant rats were randomly divided into normal group (N), mifepristone treated group (M), irisin group (I) and progestin group (P). The implantation failure model was established using mifepristone. Second, we evaluated the average number of embryos and detected the expression of LIF and integrin αvβ3 protein and mRNA in endometrium. Results Compared with group M, the average number of embryos was significantly higher in group N, P and I, the expression of LIF and integrin αvβ3 in endometrium was significantly higher in group N, P and I. Conclusion Irisin could improve the poor receptive state of endometrium by promoting LIF and integrin αvβ3 secretion to improve blastocyst implantation in rats of implantation failure.